Полная история России с древнейших времен до наших дней (Вече, 2011)
Экземпляры: ЧЗ (20151026) / Инвентарный номер: 43324 / Цена: 288.53 / Сис.шифр: 63.3(2) / Авт.знак: П 49 / ГРНТИ: 03 / ББК: 63.3(2)